Resistant cumin cultivar, GC-4 counters Fusarium oxysporum f. sp. cumini infection through up-regulation of steroid biosynthesis, limonene and pinene degradation and butanoate metabolism pathways - Dharajiya, Darshan T.; Shukla, Nitin; Pandya, Maharshi; Joshi, Madhvi; Patel, Amrutlal K.; Joshi, Chaitanya G. (Frontiers in Plant Science, 2023)
Cumin (Cuminum cyminum L.), an important spice crop belonging to the Apiaceae family is infected by Fusarium oxysporum f. sp. cumini (Foc) to cause wilt disease, one of the most devastating diseases of cumin adversely affects its production. As immune responses of cumin plants against the infection of Foc are not well studied, this research aimed to identify the genes and pathways involved in responses of cumin (cv. GC-2, GC-3, GC-4, and GC-5) to the wilt pathogen. Differential gene expression analysis revealed a total of 2048, 1576, 1987, and 1174 differentially expressed genes (DEGs) in GC-2, GC-3, GC-4, and GC-5, respectively. In the resistant cultivar GC-4 (resistant against Foc), several important transcripts were identified.These included receptors, transcription factors, reactive oxygen species (ROS) generating and scavenging enzymes, non-enzymatic compounds, calcium ion (Ca 2+ ) transporters and receptors, R-proteins, and PR-proteins. The expression of these genes is believed to play crucial roles in conferring resistance against Foc. Gene ontology (GO) analysis of the up-regulated DEGs showed significant enrichment of 19, 91, 227, and 55 biological processes in GC-2, GC-3, GC-4, and GC-5, respectively. Notably, the resistant cultivar GC-4 exhibited enrichment in key GO terms such as 'secondary metabolic process', 'response to reactive oxygen species', 'phenylpropanoid metabolic process', and 'hormone-mediated signaling pathway'. Furthermore, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed the enrichment of 28, 57, 65, and 30 pathways in GC-2, GC-3, GC-4, and GC-5, respectively, focusing on the up-regulated DEGs. The cultivar GC-4 showed enrichment in pathways related to steroid biosynthesis, starch and sucrose metabolism, fatty acid biosynthesis, butanoate metabolism, limonene and pinene degradation, and carotenoid biosynthesis. The activation or up-regulation of various genes and pathways associated with stress resistance demonstrated that the resistant cultivar GC-4 displayed enhanced defense mechanisms against Foc. These findings provide valuable insights into the defense responses of cumin that could contribute to the development of cumin cultivars with improved resistance against Foc.